Pengaruh Bukti Fisik, Empati, Kehandalan, Jaminan, Dan Daya Tanggap Terhadap Kepuasan Nasabah Bank Sampah Desa Watuaji - Nabila, Azahra (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
The iwaste ibank iis ione iof ithe iefforts ito iencourage ithe icommunity ito iplay ian iactive irole iin imanaging iwaste. iOne iof ithe iwaste ibank imechanisms iis ihousehold-scale iwaste isegregation. iSegregation iof ihousehold iwaste ithat iis iincluded iin ithe icategory iof iorganic iwaste ican ibe iused ias icompost, iwhile iinorganic ihousehold iwaste iis isaved iin ia iwaste ibank ito ibe irecycled iand ican ibe iused ias imaterial iwith ieconomic ivalue. iThis istudy iaims ito idetermine ithe ieffect iof iPhysical iEvidence, iEmpathy, iReliability, iAssurance, iand iResponsiveness ion iCustomer iSatisfaction iof ithe iWatuaji iWaste iBank. iThis iresearch iuses ia isample iof i70 irespondents iwho iare icustomers iof ithe iWatuaji iVillage iGarbage iBank. iQuantitative ianalysis itechnique iwith imultiple ilinear ianalysis iis iused iin ithis istudy. iStatistical itests icarried iout iin ithis istudy iwere ivalidity itests, ireliability itests, ipartial itests, isimultaneous itests iand idetermination itests. iThrough ithe idetermination itest, iit iwas ifound ithat iphysical ievidence, ireliability, iempathy, iassurance iand iresponsiveness ihad ian ieffect iof i14.7% ion icustomer isatisfaction iand ithe irest iwere iinfluenced iby iother ivariables inot iexamined iin ithis istudy.